Facile fabrication of flexible and adhesive micro-supercapacitor tapes from conducting polymer solution for self-powered wearable sensing system - Yuan, Wenxiong; Zhao, Chen; Zhang, Xiaoxian; Min, Yonggang; Shu, Kewei (Frontiers in Materials, 2023)
Flexible micro-supercapacitor (MSC) with in-plane electrodes has attracted significant attention as microscale energy storage devices. Especially, flexible MSCs with adhesion properties are of great interest for wearable electronics. Here, we demonstrate a facile and cost-effective mask-assisted drop-casting method to fabricate adhesive MSC on medical tape using dimethyl sulfoxide (DMSO) doped poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) aqueous solution. The fabricated MSC with poly(vinyl alcohol)/H3PO4 gel electrolyte exhibits an areal specific capacitance of 10.96 mF cm-2 at a current density of 0.1 mA cm-2 with excellent mechanical flexibility. The MSC can be attached on various substrates due to the stickiness of the medical tape. For practical application, the MSC can be coupled with a solar cell to achieve a stand-alone power supply system for a flex senor in monitoring finger movements. Therefore, we believe that the mask-assisted drop-casting method paves a new way to develop flexible and adhesive MSCs for self-powered integrated wearable electronics.